ASPEK E-FILING DENGAN KETAATAN WAJIB PAJAK MELALUI MODERASI KECAKAPAN INTERNET DAN BIAYA KETAATAN - Asbi Amin; Andi Marlinah; Sukmawati Sukmawati (AkMen JURNAL ILMIAH, 2021)
The purpose of this research was to analyze e-filing effect on taxpayer compliance, to analyze e-filing effect on mandatory compliance through moderation of internet skills and to analyze e-filing effect on taxpayer compliance without being moderated by compliance costs. Data were collected questionnaires which were distributing to the sample with accidental sampling technique to 100 individual taxpayers at KPP Makassar Barat. Data analysis using the Moderated Regression Analysis (MRA) approach. The results of the study found that the application of e-filing positively and significantly affects taxpayer compliance, internet proficiency as moderating the relationship between e-filing and taxpayer compliance, while compliance costs do not moderate the relationship between e-filing and taxpayer compliance.